Bmo‐miR‐2780a regulates the expression of the sericin‐1 gene of Bombyx mori. Issue 2 (7th November 2019) - Qian, Ping; Wang, Xin; Li, Jiashuang; Jiang, Tao; Tang, Xudong; Huixiang, Guan; Shen, Xingjia
Abstract: Silk production in Bombyx mori L. is largely determined by the expression of genes encoding fibroin and sericin. Here, we examined the regulatory function of a microRNA (miRNA) on silk gene expression using the sericin‐1 gene ( BmSer–1 ). First, we downloaded whole mature miRNAs of silkworm from miRBase and identified bmo‐miR‐2780a as a candidate miRNA for the regulation of BmSer‐1 expression. We used semi‐quantitative reverse transcription polymerase chain reaction (RT‐PCR) with stem‐loop primers to investigate the expression profile of bmo‐miR‐2780a and its predicted target gene BmSer‐1 in seven different tissues from 5th instar day‐3 larvae, including head, fat body, anterior silk gland (ASG), middle silk gland (MSG), posterior silk gland (PSG), middle gut, and hemolymph. Our results showed that bmo‐miR‐2780a was specifically expressed in the MSG and that the expression level of BmSer‐ 1 was significantly higher in the MSG than in other tissues. Recombinant plasmids carrying both pri‐mir‐2780a and Ser1 –3′UTR were constructed and then used to cotransfect BmN cells. We further detected the effect of bmo‐miR‐2780a on Ser‐1 in vivo. These results showed that the target gene was significantly decreased by miR‐2780a compared with the control group ( p <  .05), thus indicating that bmo‐miR‐2780a might negatively regulate the expression of Ser‐1 . Abstract : Bmo‐miR‐2780a negatively regulates the expression of BmSer1 in the middle silk gland of Bombyx mori .